2014
DOI: 10.1001/jamadermatol.2014.394
|View full text |Cite
|
Sign up to set email alerts
|

Asteatotic Eczema in Hypoesthetic Skin

Abstract: Asteatotic eczema developing on skin with altered sensation is an underreported condition. Prompt recognition and treatment may lead to a more efficient patient encounter and alleviate unnecessary patient stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
0
6
0
2
Order By: Relevance
“…The asteatotic eczema that developed on both the grafted and the donor site also involves disturbances of skin barrier function and dysregulated immune response. There seems to be an association to hypoesthetic skin (Cassler, Burris, & Nguyen, 2014 (Piccolo et al, 2016).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The asteatotic eczema that developed on both the grafted and the donor site also involves disturbances of skin barrier function and dysregulated immune response. There seems to be an association to hypoesthetic skin (Cassler, Burris, & Nguyen, 2014 (Piccolo et al, 2016).…”
Section: Discussionmentioning
confidence: 90%
“…The asteatotic eczema that developed on both the grafted and the donor site also involves disturbances of skin barrier function and dysregulated immune response. There seems to be an association to hypoesthetic skin (Cassler, Burris, & Nguyen, ). The sectorial impairment of immune and other functions of skin arising in the recipient as well as the donor site are examples of Ruocco's ICDs.…”
Section: Discussionmentioning
confidence: 99%
“…Defects in releasing ceramide from the lamellar bodies result in improper water barrier formation. The scar tissue formed post-surgery may impact the role of the granular layer, which is protective and lubrication of keratin and the cutaneous ability to transport substances [ 19 ]. This explanation is in line with that provided by Webster et al who also proposed that postoperative venous stasis following trauma might constitute a risk factor for localized venous congestion and may also result in cutaneous oedema, pigmented purpura resembling inflammatory dermatitis and non-immune bullous eruption [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cutaneous autonomic nervous system plays a crucial part in regulating sweat gland function, vasomotor activity, and skin blood flow, which in turn maintain the normal skin barrier. Acetylcholine and catecholamines released from autonomic nerve endings also play an important role in keratinocyte functioning [18,19]. Madke et al [12] in 2017 suggested the term ADD for the trophic changes in the skin after denervation of various autonomic organs of the skin.…”
Section: Discussionmentioning
confidence: 99%